Comorbidity of post-traumatic stress disorder and anxiety in flood survivors: Prevalence and shared risk factors. Issue 36 (September 2017) - Dai, Wenjie; Kaminga, Atipatsa C.; Tan, Hongzhuan; Wang, Jieru; Lai, Zhiwei; Wu, Xin; Xiong, Yuan; Deng, Jing; Liu, Aizhong
Abstract : Abstract: Post-traumatic stress disorder (PTSD) and anxiety are both prevalent in trauma-related populations. However, comorbidity of these 2 psychiatric disorders has not been investigated in flood survivors. This study aimed to estimate the extent to which PTSD and anxiety co-occur in flood survivors, and identify shared risk factors for PTSD only and comorbidity of PTSD and anxiety. Individuals who experienced Dongting Lake flood in 1998 were enrolled in this study using stratified and systematic random sampling method. Information on social support, personality traits, PTSD, and anxiety was collected using self-report questionnaires. The intensity of exposure to the flood was measured by some questions. Logistic regression analyses were used to identify factors associated with PTSD only and comorbidity of PTSD and anxiety. In all, 325 participants were enrolled in this study. The prevalence of PTSD, anxiety, and comorbidity of PTSD and anxiety among survivors of the 1998 Dongting Lake flood at 17-year follow-up was 9.54%, 9.23%, and 6.15%, respectively. Furthermore, 64.52% of those with PTSD had anxiety and 66.67% of those with anxiety had PTSD. Loss of relative, injury of body, damage of house, and emotional instability were shared risk factors for PTSD only and comorbidity of PTSD and anxiety, in comparison with neither PTSD nor anxiety. Post-traumatic stress disorder only and comorbidity of PTSD and anxiety are prevalent in flood survivors, and are both related to the intensity of exposure to the flood and personality traits, indicating that integrated intervention strategies of PTSD and anxiety for flood survivors are needed.